2022
DOI: 10.1186/s12985-021-01733-7
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of nuclear factor E2-related factor 2 (Nrf2) represses the replication of herpes simplex virus type 1

Abstract: Background Nuclear factor E2-related factor 2 (Nrf2) is an important transcription factor which plays a pivotal role in detoxifying reactive oxygen species (ROS) and has been more recently shown to regulate inflammatory and antiviral responses. However, the role of Nrf2 in Herpes Simplex Virus type 1 (HSV-1) infection is still unclear. In this study, the interaction between the Nrf2 and HSV-1 replication was investigated. Methods The levels of oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Lee et al also observed that Nrf2 played a role in cell viability during infection under oxidative stress but not under normal culture conditions ( 46 ). Nrf2 activation has also been associated with an antiviral program and repression of herpes simplex virus 1 replication ( 52 , 53 ). In our findings, total Nrf2 levels were decreased during the late stage of infection (72 hpi) but stabilized with ARP101 ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al also observed that Nrf2 played a role in cell viability during infection under oxidative stress but not under normal culture conditions ( 46 ). Nrf2 activation has also been associated with an antiviral program and repression of herpes simplex virus 1 replication ( 52 , 53 ). In our findings, total Nrf2 levels were decreased during the late stage of infection (72 hpi) but stabilized with ARP101 ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Other targets of HK include Sirt3 ( 19 ), Nrf2 ( 26 ), MAPK ( 27 ), and SMAD ( 28 ) signaling pathways. Some of these factors, such as Nrf2, Sirt3, and mTOR ( 29 31 ), have been linked to pathways involved in antiviral responses. HK has also been shown to possess antiviral effects against a broad range of different viruses, such as hepatitis C virus ( 16 ), dengue virus ( 15 ), herpes simplex virus 1 ( 17 ), Usutu virus ( 32 ), and Mayaro virus ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…The treatment mechanisms of BCA on HSK are still in their infancy and can be progressed in multiple aspects. Firstly, prior studies have reported that the upregulation of Nrf2 activity restricted HSV-1 viral infection [ 49 , 50 ], and isoflavones have the ability to activate Nrf2 [ 51 ]. Several studies have confirmed that BCA has the ability to activate Nrf2 [ 52 , 53 ], and our study determined it too.…”
Section: Discussionmentioning
confidence: 99%